The Effect of Strategic Orientation on Market Performance of Hotels: Empirical Evidence from the Saudi Arabia Hospitality Industry - Franklin, Udjo Eseroghene; Al-Kassem, Amer Hani (Indian Journal of Marketing, 2012)
Conclusions reached from previous studies on the effect of strategic orientation on market performance of organizations tend to converge on the notion that the customer orientation perspective is the sole effective approach to improving market performance of organizations. This study contends that this standpoint is questionable because most of the previous studies derived their conclusions based on a one-sided view of the overall strategic orientation picture. This study focusing on the hotels in the Saudi Arabia hospitality industry took a holistic examination of the subject matter. The study finds that: (a) Being customer oriented partially improves the market performance of the hotels in the Saudi Arabian hospitality industry; (b) Being competitor oriented partially improves the market performance of the hotels in the Saudi Arabian hospitality industry; and (c) Using hybrid components of the customer and competitor orientations partially improve market performance of the hotels in the Saudi Arabian hospitality industry.